Salevouris And Furay, Learning American History - Critical Skills For The Survey Course - Scott, John Anthony (Teaching History: A Journal of Methods, 1998)
This book is designed, the authors tell us, as a supplementary text and workbook for college and university students, introducing them "to the nature of history and historical thinking, the methods of historical inquiry, and the elements of effective historical writing." Varied materials are provided that allow instructors "to insert relevant skill-development and skill-assessment exercises at appropriate points in a particular course." The book's aim, they say, is to help undergraduates "attain a deeper understanding of how history is made and what it means to think 'historically.'"